Bonobo optimizer algorithm for optimum design of truss structures with static constraints. (April 2023) - Goodarzimehr, Vahid; Topal, Umut; Das, Amit Kumar; Vo-Duy, Trung
Abstract: In this study, a very recently developed intelligent algorithm called Bonobo Optimizer (BO) algorithm is implemented for the sizing optimization of the truss structures with discrete and continuous variables. The BO algorithm imitates the social behaviour and reproductive schemes of the bonobos. Like the several other primates, the bonobos also follow the fission–fusion group strategy, where they form several small parties of various sizes and move separately in their territory. The sizing optimization searches for the minimum weight of the truss structures subject to the multiple loading conditions under the required constraints on the member stresses and nodal displacements. Five well-known truss examples with fixed-geometry and up to 160 elements are tested to verify the reliability and the robustness of the BO algorithm. The results clearly indicate that the BO algorithm is a powerful search and optimization technique for the truss structures imposed by the static constraints for the discrete and continuous variables.